2018
DOI: 10.1037/xhp0000569
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous tracking of coevolving distributional regularities in speech.

Abstract: Speech processing depends upon mapping variable acoustic speech input in a manner that reflects the long-term regularities of the native language. Yet, these mappings are flexible such that introduction of short-term distributional regularities in speech input, like those arising from foreign accents or talker idiosyncrasies, leads to rapid adjustments in the effectiveness of acoustic dimensions in signaling phonetic categories. The present experiments investigate whether the system is able to track simultaneo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
39
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 21 publications
(45 citation statements)
references
References 40 publications
6
39
0
Order By: Relevance
“…Prior work thus intriguingly suggests highly specific learning arising across distributions of acoustic dimensions that is resistant to phoneme generalization and supports tracking of independent regularities across speech categories, even for the same talker (Idemaru & Holt, 2014;Maye & Gerken, 2001;Zhang & Holt, 2018). The current study further examines generalization in dimension-based statistical learning.…”
Section: Introductionsupporting
confidence: 61%
See 4 more Smart Citations
“…Prior work thus intriguingly suggests highly specific learning arising across distributions of acoustic dimensions that is resistant to phoneme generalization and supports tracking of independent regularities across speech categories, even for the same talker (Idemaru & Holt, 2014;Maye & Gerken, 2001;Zhang & Holt, 2018). The current study further examines generalization in dimension-based statistical learning.…”
Section: Introductionsupporting
confidence: 61%
“…Our prior work has repeatedly shown that the perceptual weight of the F0 dimension in voicing categorization decreases in Reverse block (Idemaru & Holt, 2011Zhang & Holt, 2018). But, we have always tested perceptual adjustment of F0 using VOT-neutral test stimuli (e.g., VOTneutral beer/pier) that aligned in the word frame with exposure stimuli (accented [b] and [p] in beer and pier).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations